The potential therapeutic effect of guanosine after cortical focal ischemia in rats. - Gisele Hansel; Denise Barbosa Ramos; Camila Aguilar Delgado; Débora Guerini Souza; Roberto Farina Almeida; Luis Valmor Portela; André Quincozes-Santos; Diogo Onofre Souza (PLoS ONE, 2014)
Background and purpose Stroke is a devastating disease. Both excitotoxicity and oxidative stress play important roles in ischemic brain injury, along with harmful impacts on ischemic cerebral tissue. As guanosine plays an important neuroprotective role in the central nervous system, the purpose of this study was to evaluate the neuroprotective effects of guanosine and putative cerebral events following the onset of permanent focal cerebral ischemia. Methods Permanent focal cerebral ischemia was induced in rats by thermocoagulation. Guanosine was administered immediately, 1 h, 3 h and 6 h after surgery. Behavioral performance was evaluated by cylinder testing for a period of 15 days after surgery. Brain oxidative stress parameters, including levels of ROS/RNS, lipid peroxidation, antioxidant non-enzymatic levels (GSH, vitamin C) and enzymatic parameters (SOD expression and activity and CAT activity), as well as glutamatergic parameters (EAAC1, GLAST and GLT1, glutamine synthetase) were analyzed. Results After 24 h, ischemic injury resulted in impaired function of the forelimb, caused brain infarct and increased lipid peroxidation. Treatment with guanosine restored these parameters. Oxidative stress markers were affected by ischemic insult, demonstrated by increased ROS/RNS levels, increased SOD expression with reduced SOD activity and decreased non-enzymatic (GSH and vitamin C) antioxidant defenses. Guanosine prevented increased ROS/RNS levels, decreased SOD activity, further increased SOD expression, increased CAT activity and restored vitamin C levels. Ischemia also affected glutamatergic parameters, illustrated by increased EAAC1 levels and decreased GLT1 levels; guanosine reversed the decreased GLT1 levels and did not affect the EAAC1 levels. Conclusion The effects of brain ischemia were strongly attenuated by guanosine administration. The cellular mechanisms involved in redox and glutamatergic homeostasis, which were both affected by the ischemic insult, were also modulated by guanosine. These observations reveal that guanosine may represent a potential therapeutic agent in cerebral ischemia by preventing oxidative stress and excitotoxicity.